VD_FINDINFO AI 32/19 - 244/2020 vom 24. Juli 2020 - VD Tribunal cantonal (2020)
DEGRÉ DE L'INVALIDITÉ, INCAPACITÉ DE TRAVAIL, CALCUL, RENTE D'INVALIDITÉ | 28 al. 1 LAI, 28 al. 2 LAI, 36 al. 2 LAI, 29bis LAVS, 29quater LAVS, 29ter LAVS, 30 al. 2 LAVS, 38 LAVS, 52b RAVS, 52c RAVS